JUE, Jeffrey K. Heaven Upon Earth: Joseph Mede (1586-1638) and the Legacy of the Millenarianism. Netherlands: Springer, 2006. 281p. - Lima, Verônica Calsoni (Revista Cadernos de Clio, 2012)
Resenha de: JUE, Jeffrey K. Heaven Upon Earth: Joseph Mede (1586-1638) and the Legacy of the Millenarianism. Netherlands: Springer, 2006. 281p.